THE EFFECT OF PRODUCT VALUE, SERVICE QUALITY, AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY AT KEDAI KOPI KENANGAN MALL OF INDONESIA - Caroline Rosa Wijaya; Innocentius Bernardo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze the relationship between product value, service quality and customer satisfaction to customer loyalty at Kopi Kenangan Mall of Indonesia. The population in this study were visitors who came to the Kopi Kenangan Mall of Indonesia from May to June 2021 and the number of samples used for the study were 200 customers that visited Kopi Kenangan Mall of Indonesia. All samples were taken by filling out a questionnaire and distributed with convenience sampling method. Data collection through questionnaires was analyzed using PLS-SEM. The results of this study showed a positive relationship between product values and customer satisfaction, a positive relationship between service quality and customer satisfaction, a positive relationship between product values and customer loyalty, a positive relationship between service quality and customer loyalty and a positive relationship between customer satisfaction and customer loyalty. Based on the results of the study, it can be concluded that customer loyalty is positively influenced by customer satisfaction and increasing product value and service quality can increase customer satisfaction. Keywords: Product Value, Service Quality, Customer Satisfaction, Customer Loyalty, Coffee Shop